Gеmotologik kasallik bilan kasallangan bеmorlarda ruhiy holatning o’zgarishi - Qurbonova G.X (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Nowadays, ensuring the health of the population in the world is not only a social but also an important economic problem in the conditions of economic growth. In this regard, special attention is paid to maintaining physical, mental and social-spiritual health from childhood. Today, attention is paid to providing medical, social and psychological support to patients with hematological diseases, for example, the head of state Sh.M. Mirziyoev, on May 14, 2021, went to the Republican Specialized Scientific and Practical Medical Center of Hematology and reported on the condition of children with gonorrhea. is a clear example. Establishing social rehabilitation centers for children with hematological diseases, studying the changes in the psychological characteristics of sick children and their relatives through the application of science.